2009
DOI: 10.4018/jesma.2009070803
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Value of Context Aware and Location Based Mobile Services

Abstract: Context aware services have the ability to utilize information about the user’s context and adapt services to a user’s current situation and needs. In this article the authors consider users’ perceptions of the added value of location awareness and presence information in mobile services. The authors use an experimental design, where stimuli comprising specific bundles of mobile services were presented to groups of respondents. The stimuli showed increasing, manipulated, levels of context-awareness, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…De Vos et al (2009) investigated the use of information about a user's context in LBSs. They found that adding context aware features to mobile services, such as location or availability, did not provide added value to users as it was offset by a user's reluctance to share location information with others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…De Vos et al (2009) investigated the use of information about a user's context in LBSs. They found that adding context aware features to mobile services, such as location or availability, did not provide added value to users as it was offset by a user's reluctance to share location information with others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(O'Grady, O'Hare & Collier, 2010) Addition of context-awareness to a mobile e-service should however be approached with caution; e.g. a study by de Vos et al (2009) on location based mobile services shows that simply adding context-awareness features to the provided service rather decreased the perceived value from a user perspective, as many users were reluctant to share context data such as location information. Privacy is of high concern when designing for context awareness.…”
Section: Availability Anywhere Anytimementioning
confidence: 99%
“…Similarly, there is a tradeoff between personalization and privacy issues in adaptive information access and such a tradeoff requires getting right balance without over profiling the users (Smyth, 2008). Vos et al (2008) developed an experimental design to figure out consumer value of location awareness and information presence in mobile services and based on experiment results, some guidelines that take into account privacy issues of consumers, consumer characteristics and concerns and service characteristics (utilitarian/ hedonic) were provided for context aware services providers. Park et al (2007) explored the effectiveness of adaptable and adaptive menus in desktop applications.…”
Section: Intelligent Mobile Servicesmentioning
confidence: 99%